Toward asset-based LatCrit pedagogies in STEM: centering Latine students’ strengths to reimagine STEM teaching and practice - Hernandez Negrete, Ambar; Mouavangsou, Kaozong N.; Caporale, Natalia (Frontiers in Education, 2023)
Latine students continue to persist in science, technology, engineering and mathematics (STEM) fields despite the numerous obstacles in place that stifle their academic potential and contributions. Instead of fostering the strengths Latine students possess that help them succeed despite these obstacles, the field of STEM education has traditionally examined these students’ experiences and challenges through a deficit lens. Deficit perspectives posit that any existing disparities in educational outcomes in STEM for Latine students are a product of the students’ lack of interest in STEM fields, poor academic preparation and/or motivation, among other ‘faults.’ In this manner, this deficit approach absolves educators, educational institutions, administrators, and researchers from any responsibility in mediating the disparate outcomes and negates the roles that outdated pedagogical practices, structural racism, discrimination and disciplinary bias have in limiting Latine students’ success in STEM. These deficit-understandings of these inequities are pervasive in all aspects of STEM education, guiding curricular choices, pedagogical approaches, assessment designs, interventions and even how STEM fields define knowledge and success. To counter these harmful constructions, this article discusses how STEM educators can draw on Latino Critical Race Theory (LatCrit) and Community Cultural Wealth (CCW) epistemologies to foster learning ecologies that draw on Latine students’ cultural strengths rather than deficits. To this end, this article introduces LatCrit and CCW frameworks in the context of STEM education, and combines them to propose an asset-based LatCrit pedagogical approach to STEM curriculum design and teaching. It also contributes guiding questions and application examples STEM educators can reference to advance asset-based LatCrit pedagogical approaches that promote justice and equity within STEM classrooms and beyond. Contributing to this underdeveloped line of scholarship in the field of STEM, we apply these critical frames to help educators (re)imagine postsecondary STEM pedagogies and reforms around the wealth of skills, dispositions, and cultural practices that Latine students possess.